Vilhelm's room : a novel - Ditlevsen, Tove Irma Margit, 1917-1976 (Farrar, Straus and Giroux, 2026)
"By the acclaimed author of the Copenhagen Trilogy, a playful and startling novel about a middle-aged women whose husband has left her"--